Development of generalized terrain-following FVCOM model for the steep terrain seas - Bu, Yixuan; Chen, Yang; Zhu, Shouxian; Zhang, Wenjing; Cao, Guangsong; Ding, Zhenguo (Frontiers in Marine Science, 2025)
Among various vertical coordinate systems, the sigma coordinate—a terrain-following approach fitted to seabed topography—has been most widely used in coastal and continental shelf seas. However, it can induce notable simulation errors in the baroclinic pressure gradient (BPG) and baroclinic currents over steep-sloped terrain. In this study, a continuous layer index function, λ, was adopted as a generalized vertical coordinate to replace the sigma coordinate in the FVCOM model. By adapting seawater motion equations suitable for the λ coordinate system, multiple forms of vertical coordinates could be flexibly configured in the FVCOM model. We designed three types of generalized terrain-following coordinates that combine conventional sigma and z coordinates for the FVCOM model (named FVCOM-gtsz) and proposed a BPG calculation scheme by subtracting the local average density stratification. Two sets of idealized seamount numerical simulation experiments demonstrated that the new coordinate systems significantly reduced simulation errors in the BPG and baroclinic currents around steep seamounts. Compared to the conventional method of subtracting area-averaged density stratification, the proposed BPG scheme more effectively eliminated errors caused by density stratification. The FVCOM-gtsz was implemented in the South China Sea, demonstrating strong performance in simulating circulation patterns, mesoscale eddy activity, and vertical thermal stratification. We further investigated the feasibility of designing density-feature-informed hybrid coordinates based on the λ coordinate system, along with other vertical coordinate formulations, which can substantially improve the FVCOM model’s adaptive operational capacity in coastal and shelf marine environments.